IMPLEMENTASI APLIKASI PENILAIAN SISWA EKSTRAKURIKULER PRAMUKA TERBAIK BERBASIS ANDROID MOBILE DENGAN METODE SMART PADA SD RAWABUNTU 3 - Bambang Wisnu Widagdo, Aldi Mahendra Prassetya (PT Triputra Sejahtera Prima, 2025)
The rapid development of technology has brought major changes in everyday life, including in the assessment process. Manual assessment with a large amount of data has a high risk of calculation errors, while there are still many other determining factors that can be considered in selecting the best scout extracurricular students. To overcome this, researchers want to develop an android-based system that implements a Decision Support System (DSS) with the SMART (Simple Multi Attribute Rating Technique) method to provide a more structured and objective assessment, so that it can help teachers in conducting transparent assessments. The research methods used include interviews with scout teachers at SD Bawabuntu 3, field observations to understand system needs and literature studies to collect data. The results of the study indicate that the application created can help facilitate teachers in assessing scout extracurricular students at SD Rawabuntu 3. The results of the analysis show that the system developed received a positive response from users, with the results of the Likert scale calculation of 82% indicating a high level of satisfaction with the assessment application, from 30 respondents.